Advances in Focal Segmental Glomerulosclerosis Treatment From the Perspective of the Newest Mechanisms of Podocyte Injury - Zhu Y; Xu G (Drug Design, Development and Therapy)
Yan Zhu,1,2 Gaosi Xu1,2 1Department of Nephrology, The Second Affiliated Hospital, Jiangxi Medical College, Nanchang University, Nanchang City, Jiangxi Province, People’s Republic of China; 2Jiangxi Key Laboratory of Molecular Medicine, The Second Affiliated Hospital of Nanchang University, Nanchang City, Jiangxi Province, People’s Republic of ChinaCorrespondence: Gaosi Xu, Email gaosixu@163.comAbstract: Podocyte injury was widely recognized as a fundamental mechanism driving the progression of focal segmental glomerulosclerosis (FSGS). Recent research has therefore focused on the development of targeted therapies aimed at disrupting specific pathogenic signaling cascades within podocytes, resulting in noteworthy advancements. The role of mechanisms such as alterations in the actin cytoskeleton, oxidative stress, mitochondrial dysfunction, and inadequate autophagy within the microenvironment of podocyte injury have garnered increasing attention. Corresponding targeted medications such as Abatacept, chemokine receptor (CCR) inhibitors, CDDO-Im (2-Cyano-3,12-dioxooleana-1,9-dien-28-imidazolide), adenosine monophosphate-activated protein kinase (AMPK) activators, and Adalimumab are currently under investigation. Notably, some medications such as Rituximab and Sparsentan, may simultaneously target multiple downstream mechanisms, Furthermore, exploring molecular strategies for established medications and developing novel treatments guided by biomarkers such as Anti-CD40 antibody, blood microRNA, urinary microRNA, and tumor necrosis factor-alpha (TNF-α) may provide additional therapeutic avenues for patients with FSGS.Keywords: focal segmental glomerulosclerosis, podocyte injury, targeted therapies, biomarkers